Α-Na2Ni2Fe(PO4)3: a dual positive/negative electrode material for sodium ion batteries. Issue 10 (5th February 2015) - Essehli, R.; Belharouak, I.; Ben Yahia, H.; Chamoun, R.; Orayech, B.; El Bali, B.; Bouziane, K.; Zhou, X. L.; Zhou, Z.
Abstract : The low temperature polymorph of Na2 Ni2 Fe(PO4 )3, crystallizing with a stuffed α-CrPO4 -type structure, plays a dual anode/cathode behaviour. Abstract : A new orthophosphate α-Na2 Ni2 Fe(PO4 )3 was synthesized using a solid state reaction route, and its crystal structure was determined from powder X-ray diffraction data. The physical properties of α-Na2 Ni2 Fe(PO4 )3 were studied by magnetic and electrochemical measurements and by Mössbauer and Raman spectroscopy. α-Na2 Ni2 Fe(PO4 )3 crystallizes according to a stuffed α-CrPO4 -type structure with the space group Imma and the cell parameters a = 10.42821(12), b = 13.19862(15), c = 6.47634(8) Å, and Z = 4. The structure consists of a 3D-framework of octahedra and tetrahedra sharing corners and/or edges with channels along [100] and [010], in which the sodium atoms are located. The 57 Fe Mössbauer spectrum indicates that the Fe 3+ cation is distributed over two crystallographic sites implying the presence of a Ni 2+ /Fe 3+ statistical disorder. Magnetic susceptibility follows the Curie–Weiss behavior above 100 K with θ = −114.3 K indicating the occurrence of predominant antiferromagnetic interactions. Electrochemical tests indicate that during the first discharge to 1 V vs. Na + /Na in a sodium cell, one Na + ion could be inserted into the α-Na2 Ni2 Fe(PO4 )3 structure. This has led to the formation of a new phase Na3 Ni2 Fe(PO4 )3 which was found to be promising as a positive electrode material for sodium batteries. When α-Na2 Ni2 Fe(PO4 )3 is further discharged to 0.03 V, it delivers a capacity of 960 mA h g −1 . This corresponds to the intercalation of more than seven sodium atoms per formula unit which is an indication of a conversion-type behaviour with the formation of metallic Fe and Ni. When cycled in the voltage range 0.03–3 V vs. Na + /Na, at 20 °C, under the current rates of 50, 100, 200, and 400 mA g −1, reversible capacities of 238, 196, 153, and 115 mA h g −1, were obtained, respectively.